Gestão do cuidado à criança com microcefalia associada ao Zika vírus: percepção de mães - Vieira, Vanessa Lopes Dativo (2019)
Introduction: The child with microcephaly associated with the Zika virus requires continuous monitoring by the services / professionals of the Network of Health Care, which guarantee the resolution of their health needs and their families. In order to ensure comprehensive care, health care management points to the need to provide and make available health technologies to meet the individual in all its complexity. Objective: to analyze the management of child care with microcephaly associated with the Zika virus in the perception of mothers. Methodology: Qualitative, descriptive-exploratory research carried out with ten mothers of children followed at two referral services in a large municipality in northeastern Brazil. The data collection took place from July to September of 2018, using a semi-structured interview. The data were submitted to thematic analysis. The project was approved by the Research Ethics Committee, opinion number 2,676,464. Results: Weaknesses in the care of the child with microcephaly associated with the Zika virus and its family, such as lack of accountability of services, lack of medicines, difficulty in accessing specialist consultations, transport, and adapted wheelchairs are noticed. The data points to an unsustainable network to address the special health needs of children / families impacted by the Zika epidemic. These fragilities made the mother realize the possible articulations in the community context and in the health care network, in order to provide for the demands of her child, in order to obtain a complete care, performing the (self) management of care. Final considerations: Child care with microcephaly associated with the Zika virus is fragmented and permeated by obstacles that make it difficult to reach the dimensions of care management, resulting in fragile management and poor resolution.